Religious Tourism: Experiences of Sikh Yatris Visting Kartarpur Corridor, Pakistan (Journal of Social Sciences Review, 2023)
Religious tourism is an important part of human culture and history. The Kartarpur Corridor in Pakistan has become a popular destination for Sikh pilgrims to attend the revered Gurdwara Darbar Sahib. This study investigated the experiences of Sikh Yatris traveling via the Kartarpur Corridor with respect to travel, logistics, living amenities, and performance of rituals. A total of 33 In-depth interviews were conducted during the period from June 2022 to July 2022 with purposively selected Sikh Yatris. Data were analyzed using thematic analysis and NVIVO 11. Sikh Yatris, who visited Kartarpur, had wonderful experiences with logistics, living amenities, and the convenience of performing religious rituals. They reported feeling a strong spiritual connection to the Kartarpur Sahib Gurdwara and expressed appreciation for the facilitation of their religious pilgrimage by the Pakistani government. Participants also reported enjoying the friendly and hospitable atmosphere in Pakistan and feeling safe and secure during their visit. This study contributes to understanding the role of religious tourism in promoting cultural exchange, interfaith dialogue, and regional stability, with the potential to normalize relations between India and Pakistan.
Keywords: Experiences; Kartarpur Corridor; Religious Tourism; Sikh Yatris